Implikasi Hukum Hak Waris Anak Berkewarganegaraan Ganda Akibat Perkawinan Campuran - Arya Rizky Safitra; Aris Munandar; Hera Alvina Satriawan (Private Law, 2023)
The purposes of this study were to know whether double citizenship child has the rights to be heir of Indonesian citizenship parent who died according to Indonesian inheritance law, and to know whether foreign citizenship child has the rights to be the heir of Indonesian citizen. Type of study was normative legal approach which applied conceptual and statute approaches. Results of the study show that, are: (1) double citizenship heir remain hold their rights to inherit from Indonesian citizens who died, based on “adat” law, Islamic law and civil law. (2). However, foreign citizen children unable to get immovable object (land) due to the provision in Art 21 Law Number 5 of 1960 on Basic Agrarian.